Social participation and mental health of immunocompromised individuals before and after COVID-19 vaccination–Results of a longitudinal observational study over three time points - Heesen, Gloria; Heinemann, Stephanie; Müller, Frank; Dopfer-Jablonka, Alexandra; Mikuteit, Marie; Niewolik, Jacqueline; Klawonn, Frank; Vahldiek, Kai; Hummers, Eva; Schröder, Dominik (Frontiers in Psychiatry, 2022)
The coronavirus disease 2019 [COVID-19] pandemic impacted how people perform their daily lives in manifold and sometimes massive ways. Particularly, individuals who are at high risk for a severe disease progression, like immunocompromised people, may have experienced drastic changes in social participation during the pandemic. A COVID-19 basic vaccination may have changed the safety behavior of immunocompromised individuals in terms of infection risk and thereby influence social participation and mental wellbeing. This study aims to investigate self-perceived social participation at baseline before and at follow-up one and six months after basic vaccination. Beginning in March 2021, 274 immunocompromised persons 18 years or older were enrolled in the COVID-19 Contact Immune study in Lower Saxony, Germany. Measurements were performed at three time points regarding social participation (Index for the Assessment of Health Impairments [IMET]), mental health (Patient Health Questionnaire-4 [PHQ-4]), subjective health status (five-point Likert-scale) and quality of life (five-point Likert-scale). In total 126 participants were included in the final analysis. About 60% of the participants showed increasing social participation over time. The greatest increase in social participation was observed within the first month after basic vaccination (p< 0.001). During the following five months, social participation remained stable. The domains “Social activities”, “Recreation and leisure” and “Close personal relationships” were responsible for the overall change in social participation. No association was found between social participation and mental health, sociodemographic or medical factors (except hypertension). It is unclear why social participation increased after basic vaccination. Perceived vaccine efficacy and a feeling of being protected by the vaccine may have caused relaxed social distancing behaviors. Reducing safety behaviors may, however, increase the risk of a COVID-19 infection for immunocompromised individuals. Further investigations are needed to explore the health-related consequences of more social participation among immunocompromised persons.